2017
DOI: 10.1111/ajo.12617
|View full text |Cite
|
Sign up to set email alerts
|

Who is and isn't having babies with Down syndrome in western Sydney: a ten year hospital cohort study

Abstract: The proportion of DS pregnancies diagnosed in the antenatal period in western Sydney could be increased by ensuring younger women are not falsely reassured that DS screening is unnecessary for them. While religious affiliation may be a factor when women decline screening, ensuring appropriate counselling remains important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Sociodemographic factors such as income, education, maternal age, rurality, and ethnicity significantly influence whether women are offered or utilise prenatal screening tests in the first instance . We found that the likelihood of a live birth with T21 was almost five times as high in the most disadvantaged women compared with the least and the majority of these women had not utilised any prenatal screening.…”
Section: Discussionmentioning
confidence: 83%
“…Sociodemographic factors such as income, education, maternal age, rurality, and ethnicity significantly influence whether women are offered or utilise prenatal screening tests in the first instance . We found that the likelihood of a live birth with T21 was almost five times as high in the most disadvantaged women compared with the least and the majority of these women had not utilised any prenatal screening.…”
Section: Discussionmentioning
confidence: 83%
“…More recently, a study from Western Sydney compared women who had a diagnosis of Down syndrome made antenatally with those whose diagnosis was made in the neonate; 25% of women in whom the diagnosis was made after birth had not been offered screening despite attending their GPs in the first trimester, or the hospital antenatal clinic, where second trimester serum screening is offered free of charge. Nearly 70% of these women not offered screening were aged <30 years, compared to just 20% of those who were offered screening.…”
Section: Discussionmentioning
confidence: 99%
“…Current programs in Australia use combined first trimester screening (CFTS) which includes maternal age, ultrasound measurement of fetal nuchal translucency and sometimes other markers, and maternal serum marker levels (β human chorionic gonadotropin plus pregnancy‐associated plasma protein A) to provide an overall risk for trisomy 21 and other aneuploidies . Second trimester triple serum screening (STSS) is available free of charge in certain hospitals when a woman has booked too late for CFTS . Non‐invasive prenatal screening (NIPT) using cell‐free fetal DNA (cfDNA) became commercially available in Australia in 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Now in 2017 in this issue of ANZJOG we have Rebecca Moses et al ., from a large multicultural pregnancy service in Western Sydney, describing the results of a retrospective cohort study of women attending for antenatal care who received a diagnosis of DS, comparing women who had a diagnosis made antenatally with those whose diagnosis was made in the neonate . Over the period 2006–2015, 59% of 129 cases of DS had an antenatal diagnosis and 41% a diagnosis following birth.…”
mentioning
confidence: 99%